Hubungan Status Sosial Ekonomi Orang Tua Terhadap Motivasi Belajar Pendidikan Jasmani Di Sekolah Dasar: Hubungan Status Sosial Ekonomi Orang Tua Terhadap Motivasi Belajar Pendidikan Jasmani Di Sekolah Dasar - Nurmaya, Nopita; Suherman, Ayi; Sudirjo, Encep (Universitas Hamzanwadi, 2025)
This study aims to determine the relationship between the socioeconomic status of parents and students' learning motivation in physical education subjects in elementary schools and to identify factors that influence the socioeconomic status of parents and students' learning motivation. The background of this study is based on the influence of socioeconomic status on students' access to learning facilities, especially in PE subjects that involve physical activity.In this study, the researcher used a correlational design with a mixed method research method, a sequential explanatory model with a non-probability sampling approach.. The sample of this study used a proportional stratified random sampling technique consisting of 30 fourth grade students from two elementary schools in Ganeas District, Sumedang Regency, selected according to the geographical location of the sub-district center. Data analysis was carried out using correlation statistical techniques to determine the extent to which the socio-economic status of parents influences students' learning motivation in physical education learning. The results of the study showed that there isthe relationship between the socio-economic status of parents and student learning motivation, although the relationship is not significant. The factors that influence the socio-economic status of parents on the motivation to learn physical education in elementary schools include:the economic conditions of parents in facilitating children's learning activities, social and environmental support, and internal factors within students such as interests and personal motivation.